(أدب الهزل عند الجاحظ) (Journal of Humanitarian and Applied Sciences, 2023)
Abstract:The topic of my research was addressed by the Arab writer Abu Othman Amr bin Bahr Al-Jahiz, who distinguished himself in the history of Arab artistic prose with his style, ideas, words, meanings, approach, and themes. Al-Abbasi, and the dispersal of humor in his books, but he singled out for him a wonderful book that is considered a rich and generous material for comic theatrical representation, which is the book (The Misers), which is full of rare artistic illustrations, and the research plan required that it be divided into a preface and four chapters, which dealt in the first chapter: Humor in literature The Arab until the era of Al-Jahiz, and included the second chapter: talking about the factors influencing the literature of humor at Al-Jahiz, and the third chapter: we tracked through it the themes of humor at Al-Jahiz, and the fourth: we devoted it to the study of irony in the literature of Al-Jahiz.
Keywords: Al-Jahiz; literature; humor; irony